Pengaruh Gaya Kepemimpinan Demokratis, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Matahari Department Store Grand Mall Bekasi (Mulia Pratama, 2023)
Human resources are a central factor in managing an organization. The achievement of an organization requires human resources as system managers. Competent human resources with good performance can support business success. Incompetent and underperforming human resources are a competitive problem that can put the company in a loss-making condition. Pt. Matahari Department Store Grand Mall Bekasi, is a retail company in Indonesia that is very competent in creating human resources who have good performance and support the success of the company. In SPSS 26 used by the researcher, with the results of multiple linear analysis tests with regression coefficient values so as to get the equation model as follows: Y = a + b1X1 + b2X2 + b3X3 which means Y = 4.963 + 0.229 X1 + 0.263 X2 + 0.465 X3. The results of the test for the coefficient of determination (R2) with a coefficient of determination (????2) is 0.757 or 75.7% of employee performance variables can be explained by the three independent variables. The results of the t statistical test with a comparison of the calculated t value with the t table on the variable. t table value of 1,999. Because the calculated t value of X1 = 2.588 and X3 = 3.067 is greater than > t table 1.999, then HO is rejected and H1 is accepted, which means that partially states "There is a significant influence between democratic leadership style on employee performance" and the calculated t value of X2 = 1.957 smaller <t table 1.999, so it can be concluded that HO is accepted and H2 is rejected, which means that partially states "there is no significant effect between democratic leadership style on employee performance" The conclusion of this study is that the results of the F test state that democratic leadership style, work motivation, and work environment together have a significant effect on employee performance, and the magnitude of the influence of these three variables can be seen in the test results for the coefficient of determination (R2) which is 75 .7%, while 24.3% was influenced by other factors outside of this study.